2023
DOI: 10.1002/ente.202300337
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency Enhancement of Biophotovoltaic Solid‐State Solar Cells

Abstract: Biophotovoltaic solid state solar cells are new friendly environmentally solar cells inspired by photosynthesis phenomena. Photosystem I, a complex protein located in the chloroplast of the plant leaves that has a principal role in light absorption, is the most common light absorber used in biophotovoltaic solid state solar cells. Low efficiency and low current density are the main challenges in this kind of solar cell. In the present study, to vacillate the motion of electrons and holes, we use carbon nanotub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Moreover, significant endeavors have been made in engineering design and experimental investigations [5,8,10,16]. Modern research evolved in understanding this green energy for sustainable use over the recent years [17][18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, significant endeavors have been made in engineering design and experimental investigations [5,8,10,16]. Modern research evolved in understanding this green energy for sustainable use over the recent years [17][18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…[ 5,6 ] Several studies have demonstrated the incorporation of light‐harvesting biomolecules into bio‐solar cells. [ 7–10 ] However, bio‐solar cells, which are exclusively operated by light‐harvesting biomolecules to generate electrical energy, have several limitations when used as an energy source. Because light‐harvesting biomolecules generally have a maximum absorption wavelength in a localized range, the bio‐solar cells utilizing them have a narrow absorption wavelength range.…”
Section: Introductionmentioning
confidence: 99%